(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The essence of e-KTP is one form of identity programmed online and is very helpful for the process of disclosing a crime, by getting instructions online through registration of population identity numbers (NIK), where first there is a district / city code, date of birth and original number. These problems can be grouped into three types of perceptions, namely: first perceptions about people’s experience of EKTP, both perceptions of community knowledge about E-KTP, thirdly Perception regarding community evaluation or evaluation of E-KTP. This study uses descriptive qualitative research methods. The research informants were 8 (eight) informants namely 1 sub-district head, 1 secretary, 1 ASN, 5 community members. Data collection techniques used are Interview Technique, Observation / Observation Technique, and Data Analysis Technique used namely Data Reduction, Data Presentation, and Conclusion Withdrawal. Based on the results of the research in Mooat Subdistrict, Bolaang Mongondow Timur Regency in the Public Perception of the implementation of E-KTP in Mooat Subdistrict, Bolaang Mongondow Timur Regency as follows: first, Perception Regarding Community Experience about E-KTP in the service process can be adequately handled and can be seen from the provisions - provisions or mechanisms in carrying out the process of providing services that are quite clear and directed, and making appropriate decisions with the issuance of special policies in minimizing delays in E-KTP services with a Record Certificate (SKP) which has the same function as E-KTP. Secondly, the Perception of Community Knowledge about E-KTP, can be handled enough that can be seen from the mechanism of E-KTP service delivery which is quite clear and also provided a special section to provide information and direction from the leadership such as the service secretary to provide services equivalent to the services provided by banks. Third, Perception Regarding Community Evaluation or Evaluation of E-KTP in the service process has been adequately addressed and can be seen from a special section to provide information to the community that came to receive services and supported by a fairly large and clear information board. Keyword : Perseption, Public, Implementation Of E-KTP Program